2008
DOI: 10.1242/jeb.014894
|View full text |Cite
|
Sign up to set email alerts
|

Occludin immunolocalization and protein expression in goldfish

Abstract: SUMMARYTight junctions (TJs) are an integral component of models illustrating ion transport mechanisms across fish epithelia; however, little is known about TJ proteins in fishes. Using immunohistochemical methods and Western blot analysis, we examined the localization and expression of occludin, a transmembrane TJ protein, in goldfish tissues. In goldfish gills, discontinuous occludin immunostaining was detected along the edges of secondary gill lamellae and within parts of the interlamellar region that line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 56 publications
3
54
0
1
Order By: Relevance
“…Therefore, expression of OCC in the intestine can be modified via feed formulations to improve the function of the cellular barrier against possible pathogens. In studies conducted on goldfish (Carassius auratus, Linnaeus 1758) [59], it has been reported that a low expression of OCC can affect the permeability of transmembrane junctions, causing a decrease in the intestinal epithelium that potentially lowers the resistance to pathogens by the redistribution of tight junction proteins, thereby altering the correct functioning of the intestinal barrier. However, the concentrations used in this study did not show an apparent negative effect on the health of the fish.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, expression of OCC in the intestine can be modified via feed formulations to improve the function of the cellular barrier against possible pathogens. In studies conducted on goldfish (Carassius auratus, Linnaeus 1758) [59], it has been reported that a low expression of OCC can affect the permeability of transmembrane junctions, causing a decrease in the intestinal epithelium that potentially lowers the resistance to pathogens by the redistribution of tight junction proteins, thereby altering the correct functioning of the intestinal barrier. However, the concentrations used in this study did not show an apparent negative effect on the health of the fish.…”
Section: Discussionmentioning
confidence: 99%
“…Samples (5-7 µg protein) were then electrophoretically separated by SDS-PAGE and western blot analysis of AeAmt1 was conducted according to a previously described protocol (Chasiotis and Kelly, 2008), while analysis of NHE3 was carried out by overnight transfer of protein to Immobilon-P polyvinylidene-difluoride (PVDF) membrane (EMD Millipore, USA) at 4°C. A custom-made polyclonal antibody that was produced in rabbit against a custom-made synthetic peptide (CPLWEREVELSDGLM) corresponding to a 14-amino acid region of AeAmt1 (GenScript USA Inc., Piscataway, NJ, USA) was used at 1:500 dilution.…”
Section: Western Blotting and Immunohistochemistrymentioning
confidence: 99%
“…Immunolocalization of AeAmt1, NKA, VA and NHE3 in paraffin-embedded sections of anal papillae was conducted according to previously described protocols (Pullikuth et al, 2006;Chasiotis and Kelly, 2008) using a 1:40 dilution of the custom-made anti-AeAmt1 antibody described above, a 1:10 dilution of a mouse monoclonal anti-α5 antibody for NKA (Douglas Fambrough, Developmental Studies Hybridoma Bank, IA, USA), a 1:100 dilution of a mouse polyclonal anti-ATP6V0A1 antibody for VA (Abnova, Taipei, Taiwan) or a 1:250 dilution of the NHE3 antibody described above. A sheep anti-mouse antibody conjugated to Cy2 or a goat anti-mouse antibody conjugated to Cy5 (Jackson Immunoresearch) was applied at 1:500 and 1:1000, respectively, to visualize NKA.…”
Section: Western Blotting and Immunohistochemistrymentioning
confidence: 99%
“…Samples were then electrophoretically separated by SDS-PAGE and western blot analysis of AeRh50 was conducted according to procedures outlined by Chasiotis and Kelly (2008). A custom-synthesized polyclonal antibody (1:2000 dilution) was raised in rabbit against the epitope HHKDDAYWETPAES corresponding to a 14-amino acid region of AeRh50-1 (GenScript USA, Piscataway, NJ, USA).…”
Section: Western Blottingmentioning
confidence: 99%